Inattention, academic underachievement, and depressive symptoms: uncovering environmental and genetic pathways from middle to late childhood - Plamondon, André; Tarabulsy, George M.; Dionne, Ginette; Ouellet-Morin, Isabelle; Vitaro, Frank; Brendgen, Mara; Boivin, Michel (Frontiers in Child and Adolescent Psychiatry, 2023)
Introduction School underachievement has been shown to mediate the association between inattention and depressive symptoms in middle childhood. However, is it not clear whether these sequential associations are underpinned by genetic and environmental pathways, and the extent to which associated disruptive behaviors, such as hyperactivity/impulsivity, and peer relation difficulties partly account for these associations. Methods The present study used a longitudinal study of twins assessed from Kindergarten to Grade 6 to address these questions using multivariate biometric modeling. Results The hypothesized genetically informed (twin) model revealed that over and above disruptive behaviors and relational difficulties, there was evidence for (1) shared genetic factors partly accounting for these associations, and for (2) putative phenotype-to-phenotype associations sequentially linking inattention, school achievement, and depressive symptoms. Discussion Confirmation of the expected sequence of phenotype-to-phenotype associations (i.e., in addition to shared genetic factors) suggests an environmental pathway linking these phenotypes. The discussion focuses on the relevance and significance of these pathways for understanding the development of school and mental health problems, as well as for the identification of children at risk and early preventive interventions.